Analysis of the Role of the Chief of Nursing for Supervision in the Implementation of Nursing Care in HoREX Baucau - da Conceição, José Ximenes; da Costa Abi, Norberto; Crisogono Gaio, Eduardo; Soares, Virgilio; Alito Pinto, Damancio (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Nursing supervision is a managerial function that plays a crucial role in ensuring the quality of healthcare services in hospitals. The Head of Nursing holds strategic responsibility to direct, guide, and evaluate the implementation of nursing care so it aligns with professional standards and patient needs. Objective: This study aimed to analyze the role of the Head of Nursing in supervising the implementation of nursing care at Horex Baucau Regional Hospital. Method: A quantitative method with a descriptive correlational design and cross-sectional approach. The population consisted of the head of nursing and team leaders in inpatient and outpatient units, with a sample of 32 nurses and technicians. Sampling used a nonprobability total sampling technique. Data were collected through questionnaires and analyzed using the Spearman rho test. Result and Discussion: The results showed a significant relationship between the role of the Head of Nursing and the implementation of nursing care, with a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.627. This shows that the better the implementation of supervision, the better the implementation of nursing care by nurses. Conclusion: In conclusion, the managerial supervision function of the Head of Nursing is essential to ensure effective nursing care and improve service quality in hospitals.